The EpiTect Methyl qPCR Assay as novel age estimation method in forensic biology - Mawlood, Shakhawan K.; Dennany, Lynn; Watson, Nigel; Pickard, Benjamin S. (Forensic science international, 2016)
•We report the first application of EpiTect Methyl qPCR system for age estimation.•Age estimation is essential in resolving a variety of forensic and non forensic question.•Outline of methods to estimate donor age using differential DNA methylation regions of gene. Human aging is associated with epigenetic modification of the genome. DNA methylation at cytosines appears currently as the best characterised modification that occurs during the mammalian lifetime. Such methylation changes at regulatory region can provide insights to track contributor age for criminal investigation. The EpiTect Methyl II PCR system (QIAGEN) was used to compare methylation levels of CpG islands in the promoter regions of a number of age related genes, of which four successfully showed changes across the lifespan (NPTX2, KCNQ1DN, GRIA2 and TRIM58). This technique is based on the detection of remaining input genome after digestion with a methylation-sensitive restriction enzyme. This study examined DNA specimens from 80 female subjects of various ages (18–91 years) obtained from blood, using primers designed to flank the studied gene loci. The data obtained from DNA methylation quantification showed successful discrimination among volunteered ages. Overall, the difference between predicted and real age was about 11 years and absolute mean differences (AMD) was only 7.2 years error. We suggest the EpiTect system can be used as fast and simple innovative tool in future forensic age estimation.